Mechanisms of micro-voids formation caused by optical breakdown in KCl single crystals under laser emission - Volosyuk, М.A. (Вопросы атомной науки и техники, 2014)
The phenomenon of optical breakdown has been studied experimentally for KCl single crystals exposed to laser emission focused on the neodymium glass with modulated quality-factor, pulse duration 5·10⁻⁸ s, wavelength λ = 1054 nm, and pulse energy of the order 1 J in the regime of local intrinsic absorption of the laser emission by the single crystal. Evaluations of local heat flash energetic constituents and characteristic durations for both local area heating and relaxation processes and following comparison with experimental results have shown that the relaxation process takes place in two stages: the first is fast phase followed by crowdion mass transfer with shock wave participation, and the second is slow phase with participation also dislocation mass transfer. Экспериментально исследовано явление оптического пробоя монокристаллов KCl сфокусированным излучением лазера на неодимовом стекле с модулированной добротностью, длительностью импульса 5·10⁻⁸ с, длиной волны λ = 1054 нм, энергией импульса порядка 1 Дж в режиме локального собственного поглощения излучения лазера монокристаллом. Оценки энергетических составляющих процесса локальной тепловой вспышки и характерных времен продолжительности разогрева локальной области и длительности релаксационного процесса и сравнение их с экспериментальными данными показали, что процесс релаксации в таких условиях протекает в две стадии: первая – быстрая, сопровождаемая краудионным массопереносом с участием ударной волны, и вторая – медленная, с участием и дислокационного массопереноса. Експериментально досліджено явище оптичного пробою монокристалів KCl сфокусованим випромінюванням лазера на неодимовому склі з модульованою добротністю, тривалістю імпульсу 5·10⁻⁸ с, довжиною хвилі λ = 1054 нм, енергією імпульсу порядка 1 Дж у режимі локального власного поглинання випромінювання лазера монокристалом. Оцінки енергетичних складових процесу локального теплового спалаху і характерного часу тривалості розігрівання локальної області і тривалості релаксаційного процесу та порівняння їх з експериментальними даними показали, що процес релаксації в таких умовах протікає в дві стадії: перша – швидка, супроводжувана краудіонним масопереносом за участю ударної хвилі, і друга – повільна, за участю і дислокаційного масопереносу.